(untitled) (Bangladesh Journal of Agriculture, 2023)
Fifteen brinjal genotypes were grown under field condition during the period from September 2019 to March 2020 to study the variation in their morphological characters. Based on the growth habit, the genotypes were classified as erect, semi-erect, and spreading types. Hair was observed generally on the leaf and stem while variability in spine, fruit color, and fruit shape were found among the genotypes. Days to first fruit harvest ranged from 79.67 to 103 days, while the leaf area ranged from 44.33 to 83.67 cm in the genotypes studied. The highest values for the fruit length and breadth had the means of 37.93 and 8.03 cm, respectively. The number of fruits per plant ranged from 9 to 23 with an average yield of 1.08 to 7.65 kg per plant. This study revealed significant morphological variations among the genotypes evaluated, which could be utilized into future breeding programs. Bangladesh J. Agri. 2023, 48(1): 123-129